2002
DOI: 10.1002/14651858.cd002958
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal discharge from hospital for healthy mothers and term infants

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
212
2
20

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(243 citation statements)
references
References 48 publications
9
212
2
20
Order By: Relevance
“…Existing literature into postnatal care highlights this challenge of giving individualised information at the right time to parents, particularly with the increasing trend of early discharge (Danbjorg et al 2014), although the impact of early discharge on many maternal and infant outcomes remains unclear (Brown et al 2002). Home visits seem to increase maternal satisfaction with postnatal care (Yonemoto et al 2013) but some women in this study wanted to be able to go back to the hospital for a longer period of time postpartum as they experienced symptoms far beyond their 6-week check-up.…”
Section: 'They Didn't Ask I Didn't Tell'mentioning
confidence: 99%
“…Existing literature into postnatal care highlights this challenge of giving individualised information at the right time to parents, particularly with the increasing trend of early discharge (Danbjorg et al 2014), although the impact of early discharge on many maternal and infant outcomes remains unclear (Brown et al 2002). Home visits seem to increase maternal satisfaction with postnatal care (Yonemoto et al 2013) but some women in this study wanted to be able to go back to the hospital for a longer period of time postpartum as they experienced symptoms far beyond their 6-week check-up.…”
Section: 'They Didn't Ask I Didn't Tell'mentioning
confidence: 99%
“…Hildingsson (Hildingsson, 2007) showed that both parents' satisfaction with early postnatal care was enhanced when fathers were given the opportunity to stay overnight at the postnatal ward and were involved in care of the newborn child. An increased understanding of fathers' perspectives is essential for the future development of postnatal care and therefore fathers should be included in research concerning the childbirth period (Brown et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst individual studies of the effect of these early discharges on women and babies have been inconclusive, Brown et al's (14) systematic review of early postnatal discharge predicted adverse outcomes for mothers and babies, such as readmissions for medical care and a possible increase in maternal and neonatal morbidity. Despite this, most maternity services have taken an early discharge approach including discharge within 6 hours of an uncomplicated birth.…”
Section: Postnatal Carementioning
confidence: 99%